2005
DOI: 10.1111/j.0022-202x.2005.23811.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomaviruses Associated with Epidermodysplasia Verruciformis in Non-Melanoma Skin Cancers: Guilty or Innocent?

Abstract: Non-melanoma skin cancers (NMSC), namely basal cell carcinomas (BCC) and squamous cell carcinomas (SCC), represent the most common form of malignancy in fairskinned populations. Solar ultraviolet radiation (UVR), immunosuppression, and genetic constitution of the host are well-known risk factors for the development of NMSC. Epidermodysplasia verruciformis (EV), a rare genetic disease associated with a high risk of skin cancer, provided the first clue to a possible role of viruses in human skin carcinogenesis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 9 publications
1
41
0
2
Order By: Relevance
“…Patients with EV are highly predisposed to infection by a specific group of HPVs and at a high risk of developing cutaneous malignant tumors, resulting from the oncogenic effects of the viruses. 29 The skin lesions appear early in childhood and are polymorphic. They are indistinguishable from flat warts when present on the face and neck, and scaly hypo or hyper-pigmented erythematous macules, similar to versicolor, when present on the trunk and limbs.…”
Section: Epidermodysplasia Verruciformis (Ev)mentioning
confidence: 99%
“…Patients with EV are highly predisposed to infection by a specific group of HPVs and at a high risk of developing cutaneous malignant tumors, resulting from the oncogenic effects of the viruses. 29 The skin lesions appear early in childhood and are polymorphic. They are indistinguishable from flat warts when present on the face and neck, and scaly hypo or hyper-pigmented erythematous macules, similar to versicolor, when present on the trunk and limbs.…”
Section: Epidermodysplasia Verruciformis (Ev)mentioning
confidence: 99%
“…Among the beta-HPVs, HPV5 and HPV8 are classified as high-risk genotypes since they are associated with skin carcinomas occurring in EV patients (151,152). It is worth stressing that beta-HPVs have been detected in trace amounts in a large proportion of nonmelanoma skin carcinomas (NMSCs) of non-EV patients, particularly those carcinomas that develop in immunocompromised individuals (57,153,165,171,202). Moreover, it has been suggested that these viruses may contribute to skin tumors in immunocompetent individuals (75), and a possible role of beta-HPV in skin carcinogenesis constitutes a hot research topic (35,76,153).…”
Section: Pathogenicitymentioning
confidence: 99%
“…The first evidence that cutaneous HPV types might play a role in the pathogenesis of cutaneous squamous cell carcinoma (SCC) was based on the detection of specific HPV types, predominantly HPV5 and HPV8 and rarely HPV types 14, 17, 20 or 47, in over 90 % of SCCs in epidermodysplasia verruciformis (EV) patients (Orth, 2005;Pfister, 2003). EV patients suffer a genetic defect that confers high susceptibility to specific HPV types that induce characteristic, macular skin lesions disseminated over the body that frequently progress to SCC.…”
Section: Introductionmentioning
confidence: 99%